Phase II Trial of Preoperative Radiation With Concurrent Capecitabine, Oxaliplatin, and Bevacizumab Followed by Surgery and Postoperative 5‐Fluorouracil, Leucovorin, Oxaliplatin (FOLFOX), and Bevacizumab in Patients With Locally Advanced Rectal Cancer: 5‐Year Clinical Outcomes ECOG‐ACRIN Cancer Research Group E3204. (29th April 2015) - Landry, Jerome C.; Feng, Yang; Prabhu, Roshan S.; Cohen, Steven J.; Staley, Charles A.; Whittington, Richard; Sigurdson, Elin Ruth; Nimeiri, Halla; Verma, Udit; Benson, Al Bowen
Abstract : Lessons Learned: The 5‐year oncologic outcomes from the trial regimen were excellent. However, the neoadjuvant and surgical toxicity of this regimen was significant and was the primary reason for the low compliance with adjuvant systemic therapy. Due to the lack of an improvement in the pathologic complete response rate, the substantial associated toxicity, and the negative phase III trials of adjuvant bevacizumab in colon cancer, this regimen will not be pursued for further study. Background: The addition of bevacizumab to chemotherapy improves overall survival for metastatic colorectal cancer. We initiated a phase II trial to evaluate preoperative capecitabine, oxaliplatin, and bevacizumab with radiation therapy (RT) followed by surgery and postoperative 5‐fluorouracil, leucovorin, oxaliplatin (FOLFOX), and bevacizumab for locally advanced rectal cancer. The purpose of this report is to describe the 5‐year oncologic outcomes of this regimen. Methods: In a phase II Simon two‐stage design study, we evaluated preoperative treatment with capecitabine (825 mg/m 2 b.i.d. Monday–Friday), oxaliplatin (50 mg/m 2 weekly), bevacizumab (5 mg/kg on days 1, 15, and 29), and RT (50.4 Gy). Surgery was performed by 8 weeks after RT. Beginning 8–12 weeks after surgery, patients received FOLFOX plus bevacizumab (5 mg/kg) every 2 weeks for 12 cycles (oxaliplatin stopped after 9 cycles). The primary endpoint was a pathologic complete response (path‐CR) rate of 30%. Fifty‐seven patients with resectable T3/T4 rectal adenocarcinoma were enrolled between 2006 and 2010. Results: Of 57 enrolled patients, 53 were eligible and included in the analysis. Forty‐eight (91%) patients completed preoperative therapy, all of whom underwent curative surgical resection. Nine patients (17%) achieved path‐CR. There were 29 worst grade 3 events, 8 worst grade 4 events, and 2 patient deaths, 1 of which was attributed to study therapy. Twenty‐six patients (54%) began adjuvant chemotherapy. After a median follow‐up period of 41 months, the 5‐year overall survival (OS) rate for all patients was 80%. Only 2 patients experienced cancer recurrence: 1 distant (liver) and 1 loco‐regional (pelvic lymph nodes), respectively. Both of these patients are still alive. The 5‐year relapse‐free survival rate was 81%. Conclusion: Despite the path‐CR primary endpoint of this trial not being reached, the 5‐year OS and recurrence‐free survival rates were excellent. However, the neoadjuvant and surgical toxicity of this regimen was significant and was the primary reason for the low compliance with adjuvant systemic therapy. Because of the lack of an improvement in the path‐CR rate, the substantial associated toxicity, and the negative phase III trials of adjuvant bevacizumab in colon cancer, this regimen will not be pursued for further study. Abstract : 摘要 背景 . 在化疗基础上联合贝伐珠单抗可改善转移性结直肠癌患者的总生存。我们在局部进展期直肠癌患者中开展了一项II期临床试验，以评价术前给予卡培他滨、奥沙利铂和贝伐珠单抗联合放疗（RT），随后进行手术，术后给予5‐氟尿嘧啶、亚叶酸和奥沙利铂（FOLFOX）及贝伐珠单抗治疗。本文旨在报告该方案5年时的肿瘤学结果。 方法 . 本项II期研究采用Simon二阶段设计，对下述治疗方案进行了评价：术前给予卡培他滨（825 mg/m 2 ，BID，周一至周五）、奥沙利铂（50 mg/m 2 ，每周一次）、贝伐珠单抗（5 mg/kg，第1、15和29天）以及放疗（50.4 Gy）；放疗后8周进行手术；术后8 ∼ 12周开始给予患者FOLFOX方案联合贝伐珠单抗（5 mg/kg）每2周一次治疗，共12周期（9周期后停用奥沙利铂）。主要终点为病理学完全缓解（pCR）率达到30%。研究在2006 ∼ 2010年共纳入57例可切除的T3/T4期直肠腺癌患者。 结果 . 入组的57例患者中有53例符合标准并纳入研究分析。48例（91%）患者完成了术前治疗，并且接受了根治切除术。9例（17%）患者达到pCR。共发生29起最严重级别为3级的不良事件以及8起最严重级别为4级的不良事件，2例患者死亡（其中1例归因于研究治疗）。26例（54%）患者开始辅助化疗。中位随访41个月后，所有患者5年总生存（OS）率为80%。仅2例患者癌症复发：1例远处转移（肝脏），1例局部区域复发（盆腔淋巴结）。这2例患者均存活。5年无复发生存率为81%。 结论 . 尽管本临床试验未能达到pCR的主要终点，但是获得了极好的5年OS率和无复发生存率。然而，该方案有明显的新辅助治疗毒性和手术并发症，这是系统性辅助治疗时依从性差的主要原因。由于未能改善pCR率、相关毒性事件较多，同时贝伐珠单抗用于结肠癌的III期临床试验获得了阴性结果，对该方案将不会开展进一步研究。 The Oncologist 2015;20:615–616